Pengaruh E-Service Quality Aplikasi MyXL Terhadap E-Satisfaction Dan E-Loyalty Pengguna Aplikasi - Muhammad Fikri Abdurrahim; Irwan Siregar (Jurnal Manajemen Strategi dan Aplikasi Bisnis, 2021)
Objective: analyze the effect of e-Service Quality of MyXL application on E-Satisfaction and e-Loyalty of application users. Research method: survey with Quantitative Approach. Methods Of Analysis: Factor Analysis, Simple Linear Regression, Multiple Linear Regression, Test F (Anova), Test T (Coefficient). Results: the results of a simple linear regression test the effect of e-satisfaction on E-loyalty R 0.914 and R2 of 0.835 can mean that the contribution of e-satisfaction to E-loyalty is 80.35% and the remaining 19.65% is another factor caused by things outside the study. The results of multiple linear regression effect of e-service quality on E-satisfaction and e-loyalty there is a correlation coefficient R value of 0.854 which means there is a strong relationship of the effect of e - service quality and e-satisfaction on e-loyalty of 85.4% while the value of the coefficient of determination of 0.730 which means the contribution of the effect of e-service quality on e-satisfaction and e-loyalty of 73% while the rest of 27% influenced by things outside the study. Conclusion: there is an effect of e-service quality on E-satisfaction and e-loyalty of application users. Suggestion: the author suggested that XL Axiata can improve user security to be safe in transactions and improve the appearance of the application to attract attention and make the appearance of the application easy to understand.